The dynamics of flourishing Indonesian Muslim families: An Interpretative Phenomenological Analysis - Afiatin, Tina; Subandi, M. A.; Reginasari, Annisa (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
Human flourishing entails a state of complete, intrinsic self-fulfillment; however, the concept also embraces interpersonal interaction through social connection. This research aims to explore the concept and dynamics of flourishing Muslim families. The data collection involved 45 to 120 minutes of in-depth interviews with five participant families. A qualitative approach was taken, with Interpretative Phenomenological Analysis (IPA) and MAXQDA 2020 techniques used to organize the data. We utilized the Ephocé and member-checking and adopted workflow protocol management tools (i.e., MAXQDA 2020) to ensure data credibility. Four superordinate themes emerged, namely compassionate love in collaboration; the adaptation process; relatedness to the larger circle beyond nuclear family members; and the role of religious and local wisdom teachings. All the themes were related to establishing the nature of a flourishing family. It is concluded that the meaning of “flourishing family” for the Indonesian Muslim Families participants emphasized shared relational well-being, which is more complex than the simple “human flourishing” concept. The findings contribute to developing the concept of a flourishing family through evidence based on empirical data regarding efforts to maintain positive potential in the family.